Chronic paracoccidioidmycosis in a woman with Crohn Disease - Tavares Dos Santos, Harim; Augusto Benevenuto de Andrade, Bruno; Fernandes, Darcy; Caxias Travassos, Daphine; Bufalino, Andreia (My University, 2017)
We report a rare case of chronic paracoccidioidomycosis(PCM) in a woman with Crohn disease in the setting of treatment with azathioprine and mesalazine. Serum tests for antigens to Paracoccidioides brasiliensis, Histoplasma capsulatum, and Aspergillus fumigatus were negative. An incisional biopsy of an oral lesion with periodic acid-schiff and Grocott-methenamine silver stains revealed chronic granulomatous inflammation with multinucleated giant cells with Paracoccidioides brasiliensis within the cytoplasm, confirming the diagnosis of PCM.